2022
DOI: 10.1002/smtd.202100947
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Metal–Support Interaction Modulation of Single‐Atom Electrocatalysts for Rechargeable Zinc–Air Batteries

Abstract: High‐performance oxygen electrocatalysts play a key role in the widespread application of rechargeable Zn–air batteries (ZABs). Single‐atom catalysts (SACs) with maximum atom efficiency and well‐defined active sites have been recognized as promising alternatives of the present noble‐metal‐based catalysts for oxygen reduction reaction and oxygen evolution reaction. To improve their oxygen electrocatalysis activities and reveal the structure–activity relationship, many advanced synthesis and characterization met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 154 publications
2
32
0
Order By: Relevance
“…It is well known that the mechanism of gas sensing involves the electron transfer or co-existence (electrical response) between gas molecules and adsorbents. Weak interactions do not induce a significant electrical response. Transition metal (TM) decoration as a cost-effective and facile method can effectively enhance their electric conductivity and electrochemical performance due to the strong interactions between gas molecules and adsorbents. Among them, the InN monolayer is considered an excellent candidate for decorating. Guo et al reported that noble metal atom (Pd, Pt, Ag, and Au)-decorated InN monolayers as a gas sensing material could cause an obvious electrical response of NO 2 adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the mechanism of gas sensing involves the electron transfer or co-existence (electrical response) between gas molecules and adsorbents. Weak interactions do not induce a significant electrical response. Transition metal (TM) decoration as a cost-effective and facile method can effectively enhance their electric conductivity and electrochemical performance due to the strong interactions between gas molecules and adsorbents. Among them, the InN monolayer is considered an excellent candidate for decorating. Guo et al reported that noble metal atom (Pd, Pt, Ag, and Au)-decorated InN monolayers as a gas sensing material could cause an obvious electrical response of NO 2 adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…By maximizing the use of atoms, creating more active sites, and learning more about the catalytic mechanism, carbon-metal composites with atomically distributed active sites have attracted increasing attention ( Wagh et al, 2020 ; Luo et al, 2021 ; Wu et al, 2022 ). For instance, a catalyst made of Cu atomically dispersed in N-doped carbon displayed remarkable ORR and kinetic performance in an alkaline solution ( Jin et al, 2021 ).…”
Section: Carbon-based Compositesmentioning
confidence: 99%
“…24,57,58 Therefore, the regulation of the interaction between the isolated metal atoms and the support provides a promising strategy for stabilizing metal SACs and strengthening the intrinsic activity to advance the electrocatalytic efficiency. [59][60][61][62] Various central metal atoms, coordination atoms, and electronic metal-support interaction (EMSI) of SACs have a great inuence on the electronic properties and charge distribution of active sites in electrocatalysis, optimizing the binding energy of intermediates, reducing the energy barrier of the ratedetermining step (RDS), and thus accelerating the electrocatalytic reaction. For example, M-N-C (M, metal)-based SACs with metals of small atomic radii (such as Cr, Mn, Fe, Co, and Ni) prefer to adsorb the C atom of CO 2 at the metal site, while those with large radii (such as Sc) coadsorb C and O for the CO 2 reduction reaction (CO 2 RRR).…”
Section: Introductionmentioning
confidence: 99%